MANAJEMEN ADMINISTRASI KELAS DALAM MENDUKUNG KETERTIBAN PEMBELAJARAN DI SEKOLAH DASAR (STUDI KASUS DI SDN 1 CILANGKAP PURWAKARTA) - Nur Widyasti Utami; Siti Nuraeni; Widia Utami; Widyaningsih, Wiwi; Supyan Sauri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of classroom administration management, analyze the conditions of learning order, and examine the role of classroom administration management in supporting learning order at SDN 1 Cilangkap, Purwakarta Regency. This research employs a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, passive participant observation, and documentation studies4. Data analysis followed the interactive model of Miles, Huberman, and Saldana, which includes data collection, condensation, display, and conclusion drawing5. The results indicate that classroom administration management at SDN 1 Cilangkap has been implemented through the functions of planning, organizing, implementing, supervising, and evaluating. Teachers prepare various administrative tools such as attendance lists, class journals, and class rules that serve as operational guidelines6. The orderly implementation of administration has proven to have a significant positive impact on learning order, characterized by increased student discipline, compliance with rules, and the creation of a conducive learning atmosphere. The primary obstacle identified is the limited technological proficiency among some senior teachers in preparing digital-based administration; however, this is addressed through mentoring and collaboration among teachers. Overall, classroom administration management is a crucial instrument in creating order and ensuring the success of the educational process in elementary schools.